2017
DOI: 10.1186/s12943-017-0613-z
|View full text |Cite
|
Sign up to set email alerts
|

KCNMA1 cooperating with PTK2 is a novel tumor suppressor in gastric cancer and is associated with disease outcome

Abstract: BackgroundInactivation of tumor suppressor genes by promoter hypermethylation plays a key role in the tumorgenesis. It is necessary to uncover the detailed pattern of whole genome-wide abnormal DNA methylation during the development of gastric cancer (GC).MethodWe performed a genome-wide methylation detection using 12 paired of GC tissues and their corresponding normal tissues. Methylation-specific PCR (MSP) and bisulphite sequencing (BSP) were used to measure methylation status of specific CpG site. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…BKCa was revealed as an important molecule in regulating contraction/relaxation of muscle cells [ 8 ], neurotransmission in the brain, and metabolism, proliferation, migration, and gene expression [ 9 ]. Although it has been described in some types of cancer cell, such as osteosarcoma [ 10 ], breast cancer [ 11 ] and gastric cancer [ 12 ], little is known about the functions of BKCa in uterus. BKCa was studied in uterus smooth muscle and was reported that BKCa is over expressed in adenomyosis tissues, and it might cause abnormal muscle contractility that induces the inflammation effects, endometrium impairment and pain [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…BKCa was revealed as an important molecule in regulating contraction/relaxation of muscle cells [ 8 ], neurotransmission in the brain, and metabolism, proliferation, migration, and gene expression [ 9 ]. Although it has been described in some types of cancer cell, such as osteosarcoma [ 10 ], breast cancer [ 11 ] and gastric cancer [ 12 ], little is known about the functions of BKCa in uterus. BKCa was studied in uterus smooth muscle and was reported that BKCa is over expressed in adenomyosis tissues, and it might cause abnormal muscle contractility that induces the inflammation effects, endometrium impairment and pain [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primer sequences of all genes are available in Supporting Table 1. The clinical characteristics of all tissue samples were presented in our previous study . The messenger RNA (mRNA) expression levels of GBAP1 and GBA in GC and adjacent normal tissues were also detected from the Gene Expression Omnibus database (GSE29272, GSE63089, GSE2685).…”
Section: Methodsmentioning
confidence: 99%
“…DNA methylation plays an important role in regulation of gene expression. Hypermethylation inhibits gene expression while hypomethylation is associated with gene activation (Irizarry et al, 2009;Thienpont et al, 2016;Ma et al, 2017;Wang et al, 2018). Using TCGA transcriptome profiles (Supplementary Table S3), we explored the association between the four-DNA methylation prognostic signature and gene expression.…”
Section: Association Of the Prognostic Signature With Gene Expressionmentioning
confidence: 99%
“…DNA methylation is a key epigenetic regulatory factor that typically results in gene silencing, playing an important role in cancer initiation and progression (Hattori and Ushijima, 2016;Koch et al, 2018). Numerous studies have shown that promoter hypermethylation is responsible for silencing of cancer tumor suppressor genes (Thienpont et al, 2016;Ma et al, 2017). Hypomethylation of oncogene promoters has also been observed in multiple types of cancer (Irizarry et al, 2009;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%